2010
DOI: 10.1007/s10311-010-0284-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, dissolution and solubility of synthetic svabite [Ca5(AsO4)3F] at 25–45°C

Abstract: Svabite is a secondary arsenate mineral, calcium fluoride arsenate [Ca 5 (AsO 4 ) 3 F], in the apatite group of phosphates. Its dissolution and subsequent release of aqueous species play an important role in the cycling of arsenic and fluoride in the environment, but the thermodynamic and kinetic properties of svabite dissolution have never been investigated. In the present study, svabite was prepared by precipitation and characterized by various techniques, and then dissolution of synthetic svabite was studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This result was consistent with the dissolution of the (Ba,Sr)SO 4 precipitates [33] and the Ca 5 (P x As 1Àx O 4 ) 3 F solid solution. [22] The calculated saturation indices for Ca 5 (PO 4 ) 3 (OH) show a distinctly different trend than those for Ca 5 (AsO 4 ) 3 (OH) (Fig. 7).…”
Section: Saturation With Respect To Calcium Phosphates and Arsenatesmentioning
confidence: 83%
See 2 more Smart Citations
“…This result was consistent with the dissolution of the (Ba,Sr)SO 4 precipitates [33] and the Ca 5 (P x As 1Àx O 4 ) 3 F solid solution. [22] The calculated saturation indices for Ca 5 (PO 4 ) 3 (OH) show a distinctly different trend than those for Ca 5 (AsO 4 ) 3 (OH) (Fig. 7).…”
Section: Saturation With Respect To Calcium Phosphates and Arsenatesmentioning
confidence: 83%
“…Therefore, from the point of view of the equilibrium thermodynamics, in solidification-stabilisation of As-containing hazardous wastes and As-contaminated soil using phosphates (apatite), large amount of phosphates (apatite) must be applied in the process to avoid the leaching of arsenic. [22] Although johnbaumite [Ca 5 (AsO 4 ) 3 OH] and other calcium arsenates have been considered for safe arsenic disposal, in treating industry and mineral processing wastes with lime, it has been assumed that these solids are extremely insoluble and stable. [11,14,23] The experimental results indicated that johnbaumite [Ca 5 (AsO 4 ) 3 OH] is stable under alkaline conditions, and in moderately soluble when compared with hydroxylapatite [Ca 5 (PO 4 ) 3 OH].…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…In the undistorted state, only the absorptions corresponding to ν3 and ν4 vibrations are observed. The two remaining fundamentals ν1 and ν2 become infrared active when the configuration of the AsO4 3ions is reduced to some lower symmetry 19 . The degenerate modes are split by distortion of the arsenate groups through lack of symmetry in the lattice sites.…”
Section: Solid Characterizationsmentioning
confidence: 99%
“…These results suggest that the composition of these final equilibrated solutions may be controlled by a surface layer having a composition distinct from that of the erythrite/ annabergite solid solution. Because of the low solubility, they dissolution kinetics were controlled by chemical reactions occurring at the mineral surface 19,20 .…”
Section: Solid Characterizationsmentioning
confidence: 99%